The meaning of the concept of “crime prevention in the customs sphere” - R. A. Cherkasskyi (Law and Safety)
The purpose of the article is to formulate the author’s vision of the concept of “crime prevention in the customs sphere”. The methodological basis of the article is a set of techniques and methods of scientific knowledge. All methods were used in conjunction and complementarity, which made it possible to achieve this goal. In the process of research, general scientific and special methods of scientific cognition were used, in particular: the philosophical method of materialist dialectics; terminological approach; system structural, comparative legal and logical legal methods. An analysis of the scientific literature shows that scholars have different interpretations of the concept of “crime prevention”, which focuses on the feasibility of understanding this definition in a broad and narrow sense. According to a broad approach to crime prevention in the customs sphere, it is regulated by the current legislation of Ukraine with socially important and useful activities of authorized entities, which is to create a safe social environment and minimize the existing destructive, especially dangerous processes, as well as expressed in systematic prevention, which finds objective coverage in a set of preventive and educational measures, tools and methods aimed at identifying the determinants of crime, their labeling, disposal, as well as building public intolerance to them. According to the narrow understanding of crime prevention in the customs sphere, there is a set of preventive and educational measures, tools and methods used by specially authorized entities to minimize the action and complete “removal” of determinants of crime in the state, as well as building collective social awareness about the special negative nature of such determinants and intolerance to them. It is generalized that crime prevention is aimed at those factors that potentially or actually lead to the manifestation of crime in society as a complex phenomenon or its individual types and kinds. These are, in particular, drug addiction, alcoholism of the population, popularization of the criminal subculture, prostitution, low level of legal awareness of the population and education in general, shortcomings in the work of public authorities and more.